Child Rights Situation Analysis Within the ASEAN Region - Petcharamesree, Sriprapha (Archīum Ateneo, 2016)
In the endeavor of promoting and protecting rights and well beings of the child, Save the Children sees the importance of having a good understanding of the situation for children in the country context in order to inform its strategic decisions at the regional level. Save the Children therefore commissioned the Institute of Human Rights and Peace Studies, Mahidol University, to carry out a comprehensive Regional Children’s Rights Situation Analysis (CRSA) in ASEAN. The overall purpose of the Regional Children’s Rights Situation Analysis is to provide a comprehensive overview and analysis of the current situation of children in ASEAN member countries. The Regional CRSA includes, among others, an examination of current rights violations and its underlying causes, including the accountabilities of duty bearers; analysis of relevant legal frameworks and of the perspectives of other stakeholders, including children, as well as, looking at the environment of changes taking place and likely to take place over the next three to five plus years and how these may affect children’s rights. The purpose is to enable Save the Children and its partner civil society organizations to make the appropriate strategic choices about what needs to be done to improve children’s lives, in the context of ASEAN and ASEAN Member States (AMS), in particular. The study has employed mainly desk reviews and a detailed study including field researches in three countries where Save the Children does not have presence (namely Brunei, Malaysia and Singapore). It also examines other sources of literatures and policy statements of ASEAN and AMS. The study also looks at emerging/new children’s rights issues or those that Save the Children in Southeast Asia has not worked on in the past so as to balance program experience with new opportunities for engagement that will have a positive impact on children’s lives. The Study Team also conducted stakeholders’ interviews and focus group discussions with children especially in the three countries as stated earlier. Two regional consultations were organized with relevant Save the Children staff as well as representatives from civil society, government and academia in ASEAN Member States. There are some limitations that the Team faced in the process of this study. The quantitative data is scarce in the region and this has implications on analyzing the disaggregation of children’s rights mapping disaggregation of data by gender, ethnicity, disability and age. The Team, to a certain extent was able to do a stakeholder analysis by looking at roles and responsibilities, capacity gap analysis, and trends analysis; however, there is room for further research.